2020
DOI: 10.1177/1947603520951627
|View full text |Cite|
|
Sign up to set email alerts
|

Observation of Solute Transport between Articular Cartilage and Subchondral Bone in Live Mice

Abstract: Objective To establish a method for investigating the permeability of calcified cartilage zone (CCZ) and to observe solute transport between articular cartilage (AC) and subchondral bone (SB) through intact CCZ in vivo. Design We developed a novel fixing device combined with un-decalcified fluorescence observation method to address the permeability of CCZ in live mice. Twenty-four Balb/c female mice aged 1 to 8 months were used to observe the development of CCZ. Eighty-four Balb/c female mice (aged 1 or 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the porous layer may facilitate transportation of mineral ions and precursors to form isolated mineral particles . Conversely, the densely packed structures have been implicated in blocking solute diffusion, which subsequently prevented vascular invasion from SB into AC, thereby enhancing pressurization of AC to resist load. , …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the porous layer may facilitate transportation of mineral ions and precursors to form isolated mineral particles . Conversely, the densely packed structures have been implicated in blocking solute diffusion, which subsequently prevented vascular invasion from SB into AC, thereby enhancing pressurization of AC to resist load. , …”
mentioning
confidence: 99%
“…26 Conversely, the densely packed structures have been implicated in blocking solute diffusion, which subsequently prevented vascular invasion from SB into AC, thereby enhancing pressurization of AC to resist load. 27,28 This distinct mineral distributions at the osteochondral interface played a major role in tissue adhesion, 6 owing to the fact that removal of minerals from the interface initiated separation of AC and SB (Figure S6a−c). To affirm this phenomenon, we prepared nanoparticle glues using 10% HAp (20 nm) in PBS (wt/v) solution to adhere to the tissues.…”
mentioning
confidence: 99%
“…The copyright holder for this this version posted October 19, 2021. ; https://doi.org/10.1101/2021.10.18.464899 doi: bioRxiv preprint solute diffusion, thus preventing the vascular invasion from SB into AC and helping pressurization of AC to resist load. 20,21 This characteristic microstructure due to distinct mineral distributions at osteochondral interface contributed a lot to tissue functions.…”
Section: Resultsmentioning
confidence: 99%
“…SEM and EDX Analyses. 200-um-thick cryo-cut samples were thawed at room temperature and washed with DI water for several times, followed by dehydrated through a graded ethanol treatments (20,30,40,50,70,80,90,95, 100 and 100 % (v/v)) for 30 min in each solution and air dried. Then, the samples were gold sputtered and imaging was performed (Hitachi SU-70) at 3 kV accelerating voltage to observe the morphology of osteochondral interface.…”
Section: Immunofluorescentmentioning
confidence: 99%
“…41 The reason may be that the permeability in natural CCZ is far less than that in adjacent tissues 3,32 because of its highly calcified status, leading to difficulties in substance exchange. 19 As a result, cartilage and subchondral bone were separated into relatively independent physiological environments by this thin structure. These independent environments that are different from the subchondral bone might help to maintain the phenotype of cartilage from degeneration, 2,42 and may provide an explanation for why the cartilage tissue in the non-CCZ group was ultimately replaced by fibrocartilage.…”
Section: Discussionmentioning
confidence: 99%